1996
DOI: 10.1002/bjs.1800830713
|View full text |Cite
|
Sign up to set email alerts
|

Early localization of necrosis by contrast-enhanced computed tomography can predict outcome in severe acute pancreatitis

Abstract: A total of 161 primary contrast-enhanced computed tomography (CT) scans of patients with acute necrotizing pancreatitis taken between 1982 and 1994 were analysed retrospectively. The aim was to assess the prognostic significance of the extent and anatomical site of pancreatic tissue necrosis in the first contrast-enhanced CT scan. The scans were obtained a mean of 2.9 days after the onset of symptoms. The pancreatic head was affected in 107 patients, the body in 119 and the tail in 138. Pancreatic tissue necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 21 publications
0
50
1
1
Order By: Relevance
“…Atlanta criteria overlook the amount and location of necrosis on CECT [7] . However, Kemppainen et al [18] showed that, the outcome was favorable for patients with necrosis restricted to the distal part of the pancreas. CECT may yield negative findings in 20%-30% of the mild AP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Atlanta criteria overlook the amount and location of necrosis on CECT [7] . However, Kemppainen et al [18] showed that, the outcome was favorable for patients with necrosis restricted to the distal part of the pancreas. CECT may yield negative findings in 20%-30% of the mild AP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the risks of acute pancreatitis are most of all infectious complications that are directly linked to the presence of necrosis, a favourable environment to the development of bacteria [3,7,[19][20][21][22][23][24][25][26][27][28]. The overall risk of infection does not exceed 10%, but in case of necrosis, it reaches 70%.…”
Section: Discussionmentioning
confidence: 99%
“…The principle benefit of early correct assessment of severity in AP is that patients who require intensive monitoring and therapy are detected at once. The role of clinical assessment is reliable but for its subjectivity the value in the early detection of severity is limited [1,6] . C-reactive protein (CRP) is a promising laboratory marker of severity, even though it is not specific for AP [1] .…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of acute pancreatitis (AP) ranges from a mild spontaneously resolved disorder to severe disease with a mortality up to 20%-48.4% [1][2][3] . sAP is defined as the AP with organ failure and/or local complications which developed from acute fluid collection (AFC) including necrosis, abscess, pseudocyst formation into or around the pancreas [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation